(NiZU^ENIE SOWREMENNYH DWIVENIJ ZEMNOJ POWERHNOSTI (B:s ((NaLMA(B-(NaTINSKIJ PROGNOSTI^ESKIJ POLIGON(B) /s - (NaLDAMVAROW(B, (NkAZBEK bAHITOWI^s; (NbREUSOW(B, (Nn(B. (Ng(B.s; (NpEREDERO(B, (Nw(B. (Ns(B.s; (NtIHOMIROW(B, (Na(B. (Nw(B.s; (NsOLOWXEW(B, (NsERGEJ lEONIDOWI^s ((NaLMA(B-(NaTA (B:s (NnAUKA(B. (NkAZssr(B,s, 1986)
(NbIBLIOGR(B.: (NS(B. 152-162 (129 (NNAZW(B.)s
(NaWT(B. (NUKAZANY NA OBOROTE TIT(B. (NL(B.s
(Nan kAZssr(B, (NiN(B-(NT SEJSMOLOGIIs
Keywords: (NgEODINAMIKAs; (NzEMLETRQSENIQs; (NpROGNOZs